Comparative Evaluation of Golden Proportion, Recurring Esthetic Dental (RED) Proportion, and Preston Proportion in Natural Dental Esthetics – A systematic review - Kini, Ashwini; Mistry, Gaurang; Parmar, Srishti; Tabassum, Rubina; Bachhav, Mayuri; Vaity, Swapnita (Journal of Neonatal Surgery, 2025)
Background: Dental esthetics play a pivotal role in enhancing facial attractiveness and patient confidence, especially in the maxillary anterior region. Theoretical models such as the Golden Proportion, Recurring Esthetic Dental (RED) Proportion, and Preston Proportion have been widely proposed to guide esthetic smile design. However, their applicability and prevalence in natural dentition across populations remain debatable. This systematic review aimed to evaluate and compare the clinical relevance and natural occurrence of these three proportions in individuals with untreated anterior maxillary teeth. Objective: To assess and compare the prevalence, consistency, and clinical utility of the Golden Proportion, RED Proportion, and Preston Proportion in natural maxillary anterior dentition across diverse populations. Methods: The review followed PRISMA 2020 guidelines and was registered in PROSPERO (CRD42024558371). A comprehensive literature search was performed across PubMed, MEDLINE, Cochrane Central, and DOAJ up to July 2024. Studies included were observational, cross-sectional, or clinical trials evaluating naturally present maxillary anterior teeth without prior restorations or orthodontic treatment. Data extraction and risk of bias assessment were conducted independently by two reviewers using standardized templates and the Newcastle-Ottawa Scale. Qualitative synthesis and meta-analysis were performed using RevMan 5.4, with heterogeneity assessed through the I² statistic. Results: Out of 957 articles initially identified, 13 studies were included in the final analysis. All included studies were cross-sectional and encompassed diverse ethnic populations from India, Iran, Turkey, Spain, Kenya, and more. The Golden Proportion showed limited natural occurrence, with compliance rates ranging from 0% to 66.7%, and was most commonly found between central and lateral incisors. The RED Proportion, though preferred by clinicians, showed inconsistent natural occurrence across studies. The Preston Proportion demonstrated the least adherence, with several studies reporting 0% compliance. No proportion demonstrated universal applicability. Meta-analytic trends confirmed significant variability across ethnicities and populations. Conclusion: None of the three evaluated proportions were consistently observed in natural dentition across all populations. While they offer conceptual frameworks for smile design, rigid application may not be clinically appropriate. A personalized, patient-specific approach—considering individual tooth morphology, facial symmetry, and esthetic expectations—is recommended over adherence to universal proportional models